The use of nano and microfibers as novel supports for the separation of biomolecules: adsorption of pDNA in different matrix-based supports - Esteves, Carolina Antunes da Costa (2015)
The use of plasmid deoxyribonucleic acid (pDNA) in the emerging gene therapy and nucleic acid based biopharmaceuticals requires pure pDNA in large quantities, so it calls for a production of safe pDNA on large scale. The main achievement of this experimental research was to find alternative matrices to pDNA purification, regarding to economical, simple and efficacy features. The choice of cellulose is due their easy and cheap obtainment and their relatively trouble-free modification; sepharose was mainly to compare results. Were tested two types of adsorption: hydrophobic interaction (is the most common and is easy and low-cost to perform) and anion-exchange (is also easy and low-cost and, generally, is more effective). The method of choice was batch adsorption, because of possible problems such as column chromatography high back pressure and poor capacity pDNA binding, furthermore is an easier method to scale-up. Through hydrophobic interaction was possible to adsorb up to 0,4 μg of pDNA per mg of cellulose microfibers gel, with ammonium sulfate 3,0 M, an enormous concentration of salt, so was concluded that the hydrophobic interaction is due to amount of salt. Through anion-exchange batch, the adorption was up to 2,5 μg of pDNA per mg of gel. Comparing with sepharose based-matrix (adorption was up to 0,7 μg of pDNA per mg of gel), cellulose microfibers are a better support, probably due the surface area expose to ligands. Factors that can be improved in these alternative matrices to pDNA purification experiments are: an increase of pDNA initial concentrations, a decrease of gel mass and, if possible, an increase of matrix surface area, i.e. a decrease of particle/fibers size.